Constructing Interconnected Microporous Structures in Carbon by Homogeneous Activation as a Sustainable Electrode Material for High-Performance Supercapacitors - Huijie Li; Rui Ma; Feifei Chen; Danting Wang; Hongmin Zhang; Chunyang Lu (Molecules, 2023)
Microporous carbon attracts attention as an electrode material for supercapacitors. However, a large number of deep and distorted mesoporous and macroporous structures are usually created by non-uniform etching, resulting in underutilized internal space. Homogeneous activation has been considered by researchers as a necessary condition for the formation of interconnected microporous structures in carbon materials. Herein, a simple strategy of hydrothermal introduction of defects followed by homogeneous activation for the preparation of microporous carbon was developed for the synthesis of electrode materials for high-performance supercapacitors. The optimized sample with defect-enriched microporous structure and large specific surface area has a specific capacity of 315 F g−1 (1 A g−1) in KOH solution, and the assembled symmetric supercapacitor achieves a high energy density of 7.3 Wh kg−1 at a power density of 250 W kg−1. This work is interesting because it not only demonstrates that rational design of electrode materials is important to boost the performance of supercapacitors, but also provides inspiration for the design of efficient supercapacitors in the future.